2011
DOI: 10.2175/106143010x12780288628570
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Methods for the Elimination of Microorganisms in Industrial Treatments: Potential Applicability to Wastewater Reuse

Abstract: Because of the growing need to eliminate undesirable microorganisms in different industrial treatments, mainly in the food and agricultural sector and the pharmaceutical industry, a number of increasingly effective systems for disinfection to eliminate microorganisms have been devised. This article analyzes different methods to eliminate and/or significantly reduce the number of microorganisms in industrial contexts and in environmental engineering. Although, in the past, thermal treatments had been used most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 111 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…EP phenomenon is exploited in electrochemotherapy (ECT) [1] – [3] ), gene electrotransfer (GET) [4] [6] ), irreversible electroporation (IRE) [7] and nanoelectroporation (NAP) [8] , among others. EP-based technologies are at present being applied to a broad spectrum of biotechnological fields, including not only medical applications but also food processing and environmental management [9] [11] . All of them share the application of electric pulses to permeabilize cell membranes, although the actual formation of pores during the process (electroporation) is at present a matter of research [12] .…”
Section: Introductionmentioning
confidence: 99%
“…EP phenomenon is exploited in electrochemotherapy (ECT) [1] – [3] ), gene electrotransfer (GET) [4] [6] ), irreversible electroporation (IRE) [7] and nanoelectroporation (NAP) [8] , among others. EP-based technologies are at present being applied to a broad spectrum of biotechnological fields, including not only medical applications but also food processing and environmental management [9] [11] . All of them share the application of electric pulses to permeabilize cell membranes, although the actual formation of pores during the process (electroporation) is at present a matter of research [12] .…”
Section: Introductionmentioning
confidence: 99%
“…A system that produces an electric field utilizing twoelectrode generates acoustic and shock waves, UV irradiation, and reactive oxygen species. Although it is unaffected by particles, this process is expensive and very effective for disinfection (Anpilov et al, 2002;Frey et al, 2013;Gusbeth et al, 2009;Poyatos et al, 2011;Yadollahpour et al, 2014).…”
Section: Pulsed Electric Fieldmentioning
confidence: 99%
“…Other essential disinfectants effective in decontaminating and inactivating viruses include chlorinebased, halogen compounds, potent oxidizing agents, and sodium hypochlorite (Chernyshov and Kolodzinska, 2020;Pradhan et al, 2020). Recently, large amounts of chlorine-based disinfectants have been widely used to control the spread of the SARS-CoV-2 outbreak in environments due to low cost and effectiveness on viral infection.…”
Section: Other Disinfectantsmentioning
confidence: 99%
“…While it is relative unaffected by particles, it is comparatively expensive (Yadollahpour et al, 2014) and electrodes can decay, requiring regular replacement. Bacterial spores are more resistant to pulsed electric fields than vegetative cells but it has been shown to be broadly effective for disinfection (Gusbeth et al, 2009;Poyatos et al, 2011;Frey et al, 2013). Haas and Aturaliye found that the application of pulsed electric fields could synergistically enhance disinfection by chlorine in river water and phosphate buffer solution, and that chlorine was in fact necessary to achieve appreciable disinfection levels (Haas and Aturaliye, 1999).…”
Section: Pulsed Electric Fieldmentioning
confidence: 99%